An Analysis of Maturity Patterns and Interest Rate Risk in Public and Private Banks in India: an Asset Liability Management Approach - Seema Kumari; Prof. Silender Singh (Journal of Corporate Finance Management and Banking System, 2024)
Asset liability management (ALM) was prioritized by the RBI for banks. In addition to attempting to match assets and liabilities according to maturities and interest rate sensitivity, ALM focuses primarily on the risk management concept. ALM assists banks in identifying the risk that results from an asset and liability mismatch. ALM uses a variety of strategies to assist banks in mitigating risk. It is dependent upon the banks' ability to estimate their risk exposures and manage risk. This paper assesses the interest rate risk and maturity patterns of 4 public and 4 private banks from March 2020 to March 2022. The analytical research and secondary data that form the basis of this study. The information was gathered from the database Indian economy. The approach of data gap analysis was employed for the analysis. The banks' maturity patterns and the effects of various interest rate scenarios on NII are examined in this study. According to the outcome, HDFC Bank exposed itself to interest risk and Canara Bank performed well in selected banks. The banks should emphasize either lowering their RSL or raising their RSA to bring down the negative gap. This study will be helpful for bank management and upcoming researchers to know the banks' profitability.